A Plasmonic Mass Spectrometry Approach for Detection of Small Nutrients and Toxins - Wu, Shu; Qian, Linxi; Huang, Lin; Sun, Xuming; Su, Haiyang; Gurav, Deepanjali D.; Jiang, Mawei; Cai, Wei; Qian, Kun (Nano-Micro Letters, 2018)
Nutriology relies on advanced analytical tools to study the molecular compositions of food and provide key information on sample quality/safety. Small nutrients detection is challenging due to the high diversity and broad dynamic range of molecules in food samples, and a further issue is to track low abundance toxins. Herein, we developed a novel plasmonic matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) approach to detect small nutrients and toxins in complex biological emulsion samples. Silver nanoshells (SiO2@Ag) with optimized structures were used as matrices and achieved direct analysis of 6 nL of human breast milk without any enrichment or separation. We performed identification and quantitation of small nutrients and toxins with limit-of-detection down to 0.4 pmol (for melamine) and reaction time shortened to minutes, which is superior to the conventional biochemical method currently in use. The developed approach contributes to the near-future application of MALDI MS in a broad field and personalized design of plasmonic materials for real-case bio-analysis. Highlights: 1 New materials-based methods. Sensitive detection of small nutrients and toxins ( pmol) was performed based on plasmonic nanoparticles. 2 Advanced analytical performance. Fast quantitation and identification of target molecules (in minutes) were directly achieved in complex emulsion samples.